How to realize large-scale outdoor thermal comfort studies? A systematic review based on OTC characterization, methods and research trends - Li, Yuan; Fei, Wenyi; Yang, Mengsheng; Wang, Yingfeng; Du, Yanan; Wang, Yaomei (Frontiers in Sustainable Cities, 2025)
IntroductionWith increasing urbanization, the frequency of extreme weather events, and the intensification of the urban heat island (UHI) phenomenon, there is a growing concern about outdoor thermal comfort (OTC) in urban and rural spaces. However, previous OTC studies have been dominated by empirical case studies of regional sample points and have lacked systematic large-scale exploration within a certain region.MethodsThis study used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method and bibliometric tools to statisticians the sources, keywords, content and highly cited papers of OTC studies.ResultsBased on the quantitative results, this study sorts and organizes OTC research from characterization, methods, and research trends, and summarizes the following results: (1) Universal thermal climate index (UTCI) is relatively suitable for large-scale OTC research; (2) The combination of subjectivity and objectivity with the application of Artificial Intelligence (AI) is the current cutting-edge research method of OTC; (3) Local climate zone (LCZ) classification system has a potential to be used in future large-scale OTC research has application potential.DiscussionBased on the collated results of previous studies, this study proposes a framework for large-scale OTC study to provide necessary theoretical support and practical guidance for future urban planning and construction, which will help optimize the urban environment and improve the thermal comfort and quality of life of residents.